Pengenalan dan Pelatihan Dasar-Dasar Matematika Pada Aplikasi Microsoft Excel - Marjono, Brigita Tri; Raharja, Danang Setiya; Salsabila, Khanza Firyal; Sylvago, Kevin Chester; Mohammad Alwin Danendra; Huri, Khotibin Sofyan Atsah; Wahyuningtyas, Emmy (Universitas Wijaya Kusuma Surabaya, 2025)
Information and Communication Technology has developed rapidly and has changed many aspects of our lives, including education. As part of the Microsoft Office application package, Microsoft Excel is very helpful for learning and data processing in educational institutions. Microsoft Exceed expectations could be a computer program that forms information naturally counting fundamental calculations, the utilize of capacities, and others. Such a handle can be wasteful since it takes a long time to calculate. Prior to Microsoft Excel, people used to perform math operations using a calculator or even calculate manually using traditional calculating tools or relying on intelligence in calculations. Therefore, training and introduction to Microsoft Excel was conducted directly by conducting discussions with several students so that they can understand that calculation operations can be quickly done by using Microsoft Excel. by conducting this discussion, students can understand for themselves and try to operate Microsoft Excel according to what has been discussed.